Blood pH and urinary uric acid-creatinine ratio in newborns with asphyxia - Sally Palit; Rocky Wilar; Ari Runtunuwu; Julius Lolombulan (Paediatrica Indonesiana, 2015)
Background Asphyxia is one of the leading causes of death in the world. Prematurity (28%), sepsis (26%), and asphyxia (23%) are the most common causes of death in newborns. In Indonesia, the newborn mortality incidence is 82 per 1,000 live births. Blood pH is a routine laboratory examination to diagnose newborn asphyxia, but it is preferrable to avoid such invasive procedures in newborns. An examination of urinary uric acid-creatinine (UA/ Cr) ratio may be useful as an alternative method for diagnosis of asphyxia. Hypoxia causes anaerobic metabolism which will increase the blood acidity, while creatinine will decline as a result of incomplete renal function in newborns. Objective To assess for a possible correlation between blood pH and urinary UA/Cr ratio in newborn asphyxia. MethodsWe conducted an observational, cross-sectional study in Prof. Dr. R. D. Kandou Hospital, Manado, North Sulawesi, from November 2013 to April 2014. Subjects were full term newborns with asphyxia. Blood pH and urinary UA/Cr ratio were compared with Pearson’s correlation test. Data was analyzed with SPSS version 22 software and P values <0.05 were considered to be statistically significant. Results Forty subjects met the inclusion criteria. Their predominant risk factor for asphyxia was fetal distress. Subjects’ mean blood pH was 7.1 (SD 0.1) and mean urinary UA/Cr ratio was 3.7 (SD 1.9). There was a moderate negative correlation between blood pH and urinary UA/Cr ratio (r= -0.55; P<0.001). Conclusion In newborns with asphyxia, lower blood pH is correlated with higher urinary UA/Cr ratio.